A membrane protein family with high potential for suitable therapies (Una famiglia di proteine di membrana con possibili potenzialità terapeutiche) - Francesco Amato (Publiediting, 2013)
The author presents an excursus of the results, obtained using advanced techniques, in researches on a membrane protein family, the G protein-coupled receptors (GCCP), that are localized on the cell membrane ad have a crucial role in many physiological processes.In detail studies aimed to identify mechanisms, biological, genetic and molecular, of the GCPR Group with opioid ligands, with particular attention to the mu-receptor, elective for the opioids with strong analgesic effects, are reported. The hypothesis is put forward that,on the basis of the already obtained results, new analgesic therapies with less undesired effects and more advantageous for the patients can be developed.